Transformation of Inclusive Physical Education Learning in Enhancing Self-Efficacy and Participation of Students with Special Needs - syahrianursaifi (CV. Abid Abadi Jaya, 2026)
This study aims to analyze the effect of the transformation of inclusive physical education learning on self-efficacy and participation of students with special needs in inclusive schools in the Kutacane region. This research employed a quantitative approach with a causal correlational design. The sample consisted of 12 students with special needs selected through purposive sampling. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using descriptive statistics and simple regression analysis. The results showed that the transformation of inclusive physical education learning scores ranged from 65 to 86 with a mean of 74.25. Student self-efficacy ranged from 70 to 89 with a mean of 76.50, while student participation ranged from 72 to 90 with a mean of 78.08. Regression analysis indicated that the transformation of inclusive physical education significantly influenced self-efficacy (p = 0.003 < 0.05) and student participation (p = 0.001 < 0.05). These findings suggest that better implementation of inclusive learning strategies leads to higher self-efficacy and participation among students with special needs in physical education. This study recommends the implementation of adaptive learning strategies and instructional differentiation in inclusive physical education to improve learning quality for students with special needs